Determination of Preventive Maintenance Time Intervals on Nail Making Machines Using Reliability Centered Maintenance (RCM) II . Method - Muhammad Arizki Zainul Ramadhan; Tedjo Sukmono (Universitas Muhammadiyah Sidoarjo, 2018)
With the increasing needs of productivity and the use of high technology in the form of machines and production facilities, the need for maintenance functions is growing. At PT. Surabaya Wire that produces nails and wires of problems that arise especially related to damage to nail making machine, it causes the hours to stop (downtime) and delay in the production process so that the engine performance becomes less effective. The purpose of the research is to determine the time interval schedule of care and know the action or maintenance activities to be done. To solve the problem in this research using Reliability Centered Maintenance (RCM) II method with Failure Modes and Effect Analyze (FMEA) calculation. RCM II defined a process used to determine what should be done for machine maintenance, whereas for FMEA it is defined as a method to identify the highest failure form on any machine malfunction. From the calculation result using FMEA and RCM II, we got treatment interval result on side shaft component (metal handlebar) with maintenance interval for 63 hours, for crank shaft component (metal road) with maintenance interval for 81 hours, and for Electric motor component with maintenance interval for 374 hours.